PERAN PARTISIPASI POLITIK PEREMPUAN ANGGOTA DPRD PROVINSI RIAU MASA BAKTI 2009-2014 - Yopi Pranoto; Risdati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The problems of women and politics in Indonesia gathered in at least four issues. The first, the representation of women is very low. Secondly, the commitment of political parties that have not gender sensitive so as not providing adequate access for the benefit of women. Third, constraints cultural values and religious teachings intrerpretasi gender bias and bias values of patriarchy. Fourth, interest, desire, interest, the women to engage in politics is low.This study aims to look at the role of the political participation of women MPs DPRD Riau Province period 2009-2014. There are several things that became the main focus in this study. That is, what are the forms of the role of political participation of women legislators Riau Province? What is the role of political participation of women legislators Riau Province effective service period 2009-2014?From the research illustrates that the role of the political participation of women councilors Riau Provincial Parliament has not been effective. Less mengusai issues concerning women. Furthermore, participation in the budgeting function performed female board members Riau Provincial Parliament is not going well. In addition, board members also unproductive woman gave birth to local regulations.Keywords: Participation, Politics, Women.